Awakening the Spirit of Political Participation: Political Literacy Strategies for Millennials - Nurmi, Nurmi; Dema, Herman; Rahmat, Muhammad Rais (Department of Government Studies, Universitas Muhammadiyah Buton., 2024)
This research explores the contribution of political literacy in enriching the political participation of the millennial generation in the Sidenreng Rappang Regency. This research collected data through observation, interviews, and documentation using a qualitative description approach. Data analysis was conducted through data reduction, data display, and conclusion drawing/verification, with processing using Nvivo12 Plus. The research findings show that political literacy plays a significant role in motivating millennial participation, as seen from the achievement of the three indicators. Although political will emerges as the dominant indicator, awareness of the importance of engaging in institutional political activity also plays an important role. Supporting factors, such as political stimuli, environmental situation, and political education, are essential catalysts for millennials' active participation. In this context, the environment and political situation are the dominant factors, outperforming other factors. The results of this study provide an in-depth understanding of the relationship between political literacy and millennials' political participation, emphasizing the role of political environment and situation as key drivers. The implications of these findings can help policy designers develop more effective strategies for improving political literacy and, consequently, increase the political participation of millennials in Sidenreng Rappang Regency.